Customer Satisfaction Analysis of Gofood In Makassar: An Integrated Approach Using CSI, IPA, and PGCV Methods - Muthia Raihana Saleha; Armin Darmawan; Agung Sutawinata (Engineering Faculty, UNSOED, 2026)
GoFood is one of the key features in the Gojek application, focusing on online food ordering and delivery, and has become a top choice among Indonesians. Alongside technological developments and rising customer expectations, measuring satisfaction and identifying service improvement priorities have become essential. This study aims to assess customer satisfaction with GoFood services in Makassar using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA), as well as to determine the order of service improvement priorities using the Potential Gain in Customer Value (PGCV) method. Data were collected from 214 GoFood users in Makassar through a questionnaire. The results show a CSI score of 75.975%, which falls into the “satisfied” category. However, the IPA and PGCV analyses indicate that several attributes still require improvement, such as accountability for damaged packaging (X17), product conformity (X9), application issues (X16), and system smoothness (X4). Although customers are generally satisfied, the findings suggest there is still potential to enhance service quality to reach the “very satisfied” level. These results are expected to serve as input for GoFood and its merchants to improve service quality continuously.